2015
DOI: 10.5194/acp-15-1901-2015
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the <sup>18</sup>O / <sup>16</sup>O ratio of UT/LMS ozone based on artefact CO in air sampled during CARIBIC flights

Abstract: Abstract. An issue of O 3 -driven artefact production of O 3 in the upper troposphere/lowermost stratosphere (UT/LMS) air analysed in the CARIBIC-1 project is being discussed. By confronting the CO mixing and isotope ratios obtained from different analytical instrumentation, we (i) reject natural/artificial sampling and mixing effects as possible culprits of the problem, (ii) ascertain the chemical nature and quantify the strength of the contamination, and (iii) demonstrate successful application of the isotop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…where p is the atmospheric pressure in bar. The coefficients a, b, and c are fit to combined datasets from Röckmann et al (1998), Stevens et al (1980), and Smit et al (1982), are obtained from Gromov (2013), and can be found in Table 2. k minor and k major are the reaction rates of the rare and abundant isotopologues respectively.…”
Section: Determination Of the Source Signaturementioning
confidence: 99%
“…where p is the atmospheric pressure in bar. The coefficients a, b, and c are fit to combined datasets from Röckmann et al (1998), Stevens et al (1980), and Smit et al (1982), are obtained from Gromov (2013), and can be found in Table 2. k minor and k major are the reaction rates of the rare and abundant isotopologues respectively.…”
Section: Determination Of the Source Signaturementioning
confidence: 99%
“…82 It is now well established [4][5][6] that the ozone MIF is not a minor and exotic phenomenon of a limited impact: its effect is photochemically transferred to many oxygen-bearing species including atmospheric CO 2 , O 2 , and water in the early solar system. 6,91,92 There is a wide area of interdisciplinary scientific fields, including atmospheric physics, geo-and cosmochemistry or climate research, 5,[93][94][95][96][97] where the ozone isotope composition, or molecular effects of isotope fractionation, plays a major role. [98][99][100] The state-of-the art of the MIF studies and possible impacts across various branches of science have been described in recent exhaustive reviews by Thiemens and Lin, 5 Thiemens et al, 20 Dauphas and Schauble, 4 and Carlstad and Boering, 6 who have concluded that ''The origin in chemical physics of the large, robustly measured mass-independent enrichments in ozone resulting from the three-body ozone formation reaction remains elusive and represents an intriguing chemical physics puzzle that deserves further study''.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established 4–6 that the ozone MIF is not a minor and exotic phenomenon of a limited impact: its effect is photochemically transferred to many oxygen-bearing species including atmospheric CO 2 , O 2 , and water in the early solar system. 6,91,92 There is a wide area of interdisciplinary scientific fields, including atmospheric physics, geo- and cosmochemistry or climate research, 5,93–97 where the ozone isotope composition, or molecular effects of isotope fractionation, plays a major role. 98–100…”
Section: Introductionmentioning
confidence: 99%